Treasury Automation: Enhancing Efficiency and Accuracy in Financial Operations. - qizi, Shаmsitdinоvа Xоnzоdа Mаrdоnbеk (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Treasury automation has emerged as a critical advancement in financial operations, promising enhanced efficiency and accuracy. This paper explores the impact of treasury automation on financial processes, identifying the technologies involved, the benefits achieved, and the challenges encountered during implementation. Empirical data from case studies and surveys highlight how automation optimizes treasury functions, providing a foundation for strategic decision-making and improved organizational performance.